Savoy cabbage (Brassica Oleracea Convar. Capitata var. Sabauda) varieties study and introduction - Turaev Sirojiddin; Ashurov Sherzod; Khaydarova Shoira; Akhrorova Munojot; Ikromova Dilafruz; Shodiyeva Navbakhor (BIO Web of Conferences)
In recent years, in the Republic of Uzbekistan, comprehensive measures have been implemented to ensure food security of the population, to fully satisfy their needs for vegetable products, and to expand the range of vegetable products. As a result, the introduction of new non-traditional vegetable crops for our people has been achieved in recent years. However, savoy cabbage has not been introduced, and insufficient attention has been paid to scientific research on the study of varieties of this non-traditional vegetable crop, the creation of new varieties and the improvement of cultivation technology. This article shows the results of the research aimed at selecting varieties suitable for growing in the open field in the future by studying savoy cabbage varieties, as well as the preparation of seedlings, stem height, number of leaves per bush, cabbage ripening day, cabbage shape, cabbage weight and diameter, yield. information about.